Implementation of electoral law and democracy in the European Union - Бискупский, Роман (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
The article considers the problem of providing local elections on the example of the state of Poland. Legal mechanisms for ensuring the electoral process at the local and regional levels are disclosed. Approaches to the categories of referendum and elections are analyzed. The place and role of the judiciary in the election process and options for enforcing judgments are disclosed. The criteria for determining the opinion of local residents, the economic and social criteria for conducting elections in the Republic of Poland are determined.